Assessment of risks of feline mismatched transfusion and neonatal isoerythrolysis in the Lyon (France) area. Issue 2 (July 2019) - Nectoux, Alexandra; Guidetti, Maryline; Barthélemy, Anthony; Pouzot-Nevoret, Céline; Hoareau, Guillaume L; Goy-Thollot, Isabelle
Objectives: The aims of this study were to update the prevalence of different feline blood types in the Lyon (France) area, as well as to determine the risk of mismatched transfusion (MT) and neonatal isoerythrolysis (NI) in kittens with parents of unknown blood type. Methods: Blood samples were obtained from blood donor cats and cats admitted to an intensive care unit in Lyon. AB blood typing was performed using an immunochromatographic strip. The risk of MT was estimated by adding the risk of a major transfusion reaction and the risk of a minor transfusion reaction. The risk of NI was estimated according the equation (p²)(q²) + 2pq(q²), with q being the b allele frequency and p = 1 – q. The results were analysed by absolute and relative frequency analysis and multivariate analysis. Results: The cohort study population included 320 non-pedigree cats and 37 pedigree cats. The prevalence of blood types A, B and AB was 84.3%, 14.0% and 1.7%, respectively. Considering non-pedigree cats, the prevalence of types A, B and AB was 83.7%, 14.4% and 1.9%, respectively. There were no significant differences of blood type distribution by sex ( P = 0.73) or by breed ( P = 0.90). Based on these percentages, the risks of MT and NI in non-pedigree cats were 24.3% and 12.3%, respectively. Conclusions and relevance: The prevalence of type B cats is high in the Lyon area and associated with high risks of MT and NI. These results confirm the importance of performing blood typing prior to any blood transfusion or mating.